Educational Interventions to Improve Atopic Dermatitis Outcomes for Children: A Systematic Review - Tamarachiara Kuntjoro; Adeline Jaclyn; Myrna Adiwijaya (Faculty of Medicine, Universitas Airlangga, 2020)
Background: Atopic dermatitis (AD) has a significant negative impact on the quality of life (QoL) of affected children and their families. Despite the availability of efficacious treatment, poor knowledge of AD treatment, and adherence to daily controller medications leads to a high rate of treatment failure. Purpose: To characterize the efficacy of educational interventions to improve AD outcomes in the pediatric population. Methods: A systematic search of PubMed, OVID Medline, CINAHL, and PsychINFO was conducted from September 2010 through September 2018. We compared populations, intervention characteristics, study designs, outcomes, settings, and intervention levels across studies. Result: Of 85 articles identified and reviewed, 7 articles met inclusion criteria. All included studies demonstrated efficacy in overall outcomes. All studies were performed in a hospital setting or utilized technology. The most common format for pediatric AD intervention delivery was the use of group lectures. Promising strategies to address time limitations in parents of children with AD include multifaceted educational support programs, individually tailored nurse consultation, and Web-Based Educational Programs. This systematic review is not a meta-analysis, therefore limiting its quantitative assessment of studies. Conclusion: Educational interventions demonstrate efficacy in improving pediatric AD outcomes. As the seven included studies employed a wide variety of outcome assessment tools, it is difficult to compare the extent of improvement in outcomes across these studies. In order to better assess the comparative efficacy of different educational interventions to improve outcomes in children with AD, it is essential to standardize outcome measures.